Design and Optimization of PLGA-Based Tribulus terrestris Loaded Nanoparticles - Azadeh Manayi; Nikoo Bagheri; Rasoul Dinarvand; Mehdi Esfandyari-Manesh; Mahnaz Khanavi* (Iranian Society of Pharmacognosy, 2022)
Background and Objectives: Novel drug delivery systems improve bioavailability of standardized plant extracts which enables them to cross the biological membranes. Biodegradable polymeric nanoparticle systems are an approach to circumvent problems in drug delivery. Tribulus terrestris growing in subtropical areas has exhibited some biological and pharmacological activities; it contains compounds like flavonoids and steroids. To improve bioavailability of active compounds of the plant, its extract was subjected to prepare nanoparticles. Methods: Aqueous ethanol 80% extract of the whole plant was used for preparation of encapsulated nanoparticles using poly DL-lactic-co-glycolic acid (PLGA) polymer. Mean particle size, polydispersity, drug loading and encapsulation efficiency of the nanoparticles systems were evaluated in various ratios of T. terrestris extract. Results: All the applied concentrations of the extract provided particles in nano-scale size (163-214 nm). By increasing the extract ratio encapsulation efficacy also increased ranging between 40.3-78.5%. Above 50% of the loaded extract released in the first 3 h and it continued for 10 days. Conclusion: the plant extract has been successfully encapsulated into PLGA polymer. The quantification of encapsulation efficiency and in vitro release also showed that application of the plant in pharmaceutical field can be improved using nanoparticles.